2023
DOI: 10.2460/ajvr.22.12.0217
|View full text |Cite
|
Sign up to set email alerts
|

Ground reaction forces, temporospatial parameters, range of motion, and limb characteristics were analyzed for small and medium size sound dogs with the use of pressure sensitive walkway

Abstract: OBJECTIVE To study ground reaction forces (GRF) and temporospatial parameters for small and medium size dogs using a pressure sensitive walkway (PSW). We hypothesized that, at a given speed, small dogs would have shorter stance time than medium dogs and that dog height (DH) would influence GRF. ANIMALS 30 healthy, sound dogs were divided into 2 groups, small < 15 kg and medium dog group weighing 15 to 25 kg. PROCEDURES GRFs were measured for both groups at walk and trot using PSW. Muscle mass and joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…techniques and report that they are equally reliable but not interchangeable [54][55][56][57]. Further, studies have shown a high agreement between repetitive measurements in individual dogs [58].…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…techniques and report that they are equally reliable but not interchangeable [54][55][56][57]. Further, studies have shown a high agreement between repetitive measurements in individual dogs [58].…”
Section: Methodsmentioning
confidence: 94%
“…Two of the previous studies have evaluated the effect of TENS by the use of kinetic techniques, i.e., pressure-sensitive mats and force plates; the latter is regarded as the gold standard for measuring ground reaction forces [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Recent studies have compared the results from these two kinetic techniques and report that they are equally reliable but not interchangeable [ 54 , 55 , 56 , 57 ]. Further, studies have shown a high agreement between repetitive measurements in individual dogs [ 58 ].…”
Section: Introductionmentioning
confidence: 99%